Long-term annual trawl data show shifts in cephalopod community in the western Barents sea during 18 years - Golikov, Alexey V.; Jørgensen, Lis L.; Sabirov, Rushan M.; Zakharov, Denis V.; Hoving, Henk-Jan (Frontiers in Marine Science, 2024)
Climate change is threatening marine ecosystems on a global scale but particularly so in the Arctic. As a result of warming, species are shifting their distributions, altering marine communities and predator-prey interactions. This is known as the Atlantification of the Arctic. Warming may favor short-lived, opportunistic species such as cephalopods, marine mollusks that previously have been hypothesized to be winners in an ocean of change. To detect temporal regional trends in biodiversity, long-term annual surveys in hotspots of climate change are an unparalleled source of data. Here, we use 18 years of annual bottom trawl data (2005–2022) to analyse cephalopods in the western Barents Sea. More specifically, our research goals are to assess temporal trends in cephalopod fauna composition, abundance and biomass, and to relate these trends to climate change in the western Barents Sea. Main changes in cephalopod diversity and distribution occurred in mid-2000s and early 2010s, which corresponds with a period of warming in the Arctic since the late 1990s/early 2000s. Repeated increased occurrence of the boreal-subtropical cephalopods was recorded from 2005–2013 to 2014–2022. Moreover, the abundance of cephalopods in the area (in general and for most taxa) increased from 2005–2013 to 2014–2022. These observations suggest that the cephalopod community of the Barents Sea is subjected to Atlantification since the 2005–2013 period. This corresponds with previously reported evidence of the Atlantification in fishes and benthic invertebrates in the Barents Sea and benthic invertebrates. ‘Typical’ Arctic cephalopod species such as Bathypolypus spp., Gonatus fabricii and Rossia spp., however, are still much more abundant in the western Barents Sea compared to the deep-sea and the boreal-subtropical species. We also found indirect indications for body-size reduction in Bathypolypus spp. from 2005–2013 to 2014–2022. Overall, the temporal trends in the Barents Sea cephalopod fauna provide evidence for changing marine communities in the Arctic.